The chemopreventive effect of taxifolin is exerted through ARE-dependent gene regulation - Lee, Saet Byoul; Cha, Kwang Hyun; Selenge, Dangaa; Solongo, Amgalan; Nho, Chu Won (PHARMACEUTICAL SOC JAPAN, 2007)
Phase II detoxification enzymes are responsible for the detoxification and elimination of activated carcinogens, and thus act as important biomarkers for chemoprevention. In this study, we tested the chemopreventive activity of taxifolin, a flavanon compound purified from a mongolian medicinal plant, by measuring quinone reductase (QR) activity in HCT 116 cells. Taxifolin induced significant QR activity, but displayed relatively low cytotoxicity in cells (chemoprevention index=5.75). To identify the target genes regulated by taxifolin, DNA microarray was performed with a 3K human cancer chip containing 3096 human genes associated with carcinogenesis. Significant analysis of microarray (SAM) revealed 428 differentially expressed (DE) genes as statistically significant, with a false discovery rate (FDR) of 57.2% (delta=0.3366). Sixty-five genes, including a few detoxification enzymes (NQ01, GSTM1) and an antioxidant enzyme (TXNRD1), were up-regulated and 363 genes were down-regulated in the presence of 60,mu m taxifolin. In view of the finding that selected genes of interest contained antioxidant response element (ARE), we hypothesize that taxifolin modulates chemopreventive genes through activation of the ARE. Transient transfection experiments using the ARE QR-CAT construct demonstrate that taxifolin significantly activates ARE, but not xenobiotic response element (XRE). In conclusion, taxifolin acts as a potential chemopreventive agent by regulating genes via an ARE-dependent mechanism.
Keywords: OXIDOREDUCTASE NQO1 GENE; S-TRANSFERASE M1; TRANSCRIPTIONAL REGULATION; INDUCIBLE EXPRESSION; ENZYME INDUCERS; NULL GENOTYPE; FLAVONOIDS; CANCER; REDUCTASE; RISK